Association of vitamin D in patients with periodontitis: A cross‐sectional study - Isola, Gaetano; Alibrandi, Angela; Rapisarda, Ernesto; Matarese, Giovanni; Williams, Ray C.; Leonardi, Rosalia (Journal of periodontal research, 2020)
Background and Objective Vitamin D has been considered to possess anti‐inflammatory and antimicrobial activity, which may be a link for the known interaction of periodontitis (CP) and coronary heart disease (CHD). This study investigated the association between serum vitamin D levels and periodontitis in patients with CP and with CHD. Furthermore, the objective was to determine whether periodontitis and CHD had an impact on serum vitamin D levels. Material and Methods Using a cross‐sectional design, a total of 46 patients with CP, 45 patients with CHD, 45 patients with both CP and CHD, and 43 healthy patients were enrolled in the present study. Results Patients in the CP (17.4 ± 5.2 ng/mL) and in the CP + CHD (16.5 ± 5.6 ng/mL) group presented a significantly lower mean serum level of 25(OH)vitamin D compared to patients in the CHD (24.6 ± 3.7 ng/mL) and healthy control groups (29.9 ± 5.4 ng/mL) (P < .001). 25(OH)vitamin D levels were positively correlated with the number of teeth and negatively with C‐reactive protein (CRP) and all periodontal parameters (P < .001). In all patients, there was a proportional increase of 25(OH)vitamin D levels with a progressive increase in number of teeth (P‐trend <.001) while there were a proportional decrease in 25(OH)vitamin D levels with a progressive increase in clinical attachment level (CAL, P‐trend = .001), probing depth (PD, P‐trend = .006), and bleeding sites (BOP, P‐trend <.001) levels. Conclusion Patients with CP and CP + CHD presented significantly lower serum levels of vitamin D compared to CHD and healthy controls. Moreover, the presence of CP negatively influenced serum vitamin D levels.